HUBUNGAN TINGKAT STRES DAN STRATEGI KOPING DENGAN PRESTASI AKADEMIK PADA MAHASISWA KEPERAWATAN REGULER DI SEKOLAH TINGGI ILMU KESEHATAN X TAHUN 2017 - Rusita Ari Wibowo; Dewa Ayu Sri Saraswati (Jurnal Kesehatan STIKes IMC Bintaro, 2018)
Stress and coping strategies are things that can be perceived by all walks of life among college students, trying to get a good GPA score. The stressed students in the United States 47%, the UK 31.2%, Malaysia 61.4%. This study aims to determine the relationship between stress level and coping strategies with the regular academic achievement of nursing students in STIKes X 2017. This study used cross sectional design. The sample was chosen by total sampling method as many as 85 respondents. Data collection used stress measurement instruments and coping strategies in the form of PSS-10 and Brief Cope questionnaires. Data were analyzed by using chi square test. The result of univariate analysis showed that male respondents were 8 (9.4%) and female 77 (90.6%). Based on late adolescence age of 27 (32.9%) and early adult 57 (67.1%). The result of bivariate analysis of chi square test between stress level and GPA value got p value = 0.600, while bivariate between coping strategy and GPA value got p value = 0.004 with OR = 6,359. There is no relationship between stress level and academic achievement. There is a relationship between coping strategies and academic achievement. Students are able to recognize stress and use appropriate coping strategies in the process of achievement